TOXICOLOGICAL EVALUATION OF A MONOAMMONIUM PHOSPHATE FERTILIZER IN RATS FOLLOWING 30 DAYS OF REPEATED ORAL EXPOSURE - Araar Samia; Khaldi Fadila; Sayah Sarra; Chaib Sakina; Gheid Abdelhak (Fresenius Environmental Bulletin, 2022)
The present study was undertaken to evaluate the subacute toxicity of a synthetic fertilizer widely used in agriculture (Phosfert®, monoammonium phosphate NH4H2PO4 (MAP)) on some haematolog-ical and biochemical profiles as well as liver and kid-ney histology in Wistar rats. MAP was administered to rats orally at 200, 400, and 800mg/kg of body weight doses for 30 days. Results showed decreased body weight and a significant increase in liver and kidney relative weights in MAP-treated rats. In ad-dition, hematotoxicity effect of high doses of MPA was evidenced by decreased levels of red blood cells (RBC), haemoglobin (Hb) and hematocrit (Ht) along with increased levels of white blood cell (WBC) counts. Further, hepatic and renal markers and lipid profiles were markedly increased however; total pro-teins and albumin levels were considerably de-creased in MAP treated rats as compared with con-trols. These effects were supported by the liver and kidney histopathological evaluations. Conclusively, the study proved that the long-term use and at higher doses of MAP may cause adverse hepatic and renal effects